Timing of diagnosis of gestational diabetes and pregnancy outcomes: A retrospective cohort. (19th April 2018) - Shub, Alexis; Chee, Tess; Templeton, Alexandra; Boyce, Deborah; McNamara, Catharine; Houlihan, Christine; Churilov, Leonid; McCarthy, Elizabeth A.
Abstract : Background: Recent guidelines suggest screening high‐risk women in early pregnancy for gestational diabetes (GDM); however, there is little evidence to support this. Aims: To compare pregnancy outcomes associated with diabetes for women with risk factors for GDM according to gestation of diagnosis. Early GDM was defined as a positive test before 20 weeks gestation, late GDM as a positive test at 20 or more weeks and no GDM when both tests were negative. Materials and methods: Retrospective analysis in an Australian tertiary hospital of women who underwent a glucose tolerance test in pregnancy prior to 20 weeks gestation, and a repeat test after 20 weeks gestation if the initial test was negative. Results were adjusted for maternal demographics. Results: Women with early GDM ( n  =   170) were no more likely to experience the obstetric composite outcome than women with late GDM ( n  =   171) or no GDM ( n  =   547) (early odds ratio (OR) 1.16, 95%CI 0.79–1.71; late OR 0.78, 95%CI 0.53–1.12). Infants of women with early GDM, but not late GDM, were more likely (early OR 1.8, 95%CI 1.15–2.92; late OR 1.4, 95%CI 0.90–2.23) to have the neonatal composite outcome than infants of women without GDM, predominantly due to an increase in neonatal hypoglycaemia. Conclusions: This result may be due to careful management of GDM, or because, after adjustment for maternal demographics, the early diagnosis of GDM does not substantially increase rates of adverse outcomes compared to GDM diagnosed in later pregnancy or no GDM in women with risk factors for GDM.